Psoriasis: Best Case Series - Gupta, Girish; Gupta, Naveen; Pandey, Dileep Kumar; Gupta, Gaurang (Homœopathic Links, 2019)
Psoriasis is a chronic, non-contagious, autoimmune disease. A case series of five patients successfully treated by homoeopathy is presented herewith to acquaint the homoeopathic professionals about the effectiveness of single individualised constitutional homoeopathic medicine in the treatment of psoriasis.
Keywords: psoriasis; autoimmune disease; individualised homoeopathic medicine